Iceland’s Involvement in the Anti-Apartheid Struggle - Einarsdóttir, Jónína (Stjórnsýslustofnun, 2016)
The transnational anti-apartheid movement was heavily motivated by the postwar emphasis on human rights and decolonisation, and challenged by Cold War politics and economic interests. The aim of this article is to examine Iceland’s involvement in the anti-apartheid struggles with focus on the establishment of the unified anti-apartheid movement SAGA (Suður-Afríkusamtökin gegn apartheid), its organisation and activities. What were the motives of SAGA’s activists and their subjective experiences? The political background in Iceland is outlined as well as a historical overview of anti-apartheid activities including Iceland’s voting on resolutions against apartheid at UN and adoptions of sanctions against the South African regime. Iceland’s involvement in the antiapartheid struggle was contradictory. During two periods Iceland voted for more radical UN resolutions than did other Western countries, including the Nordic ones. Yet, Iceland adopted sanctions against the South African regime later than the neighbours and the same applies to the establishment of a unified anti-apartheid movement. The branding of the African National Congress (ANC) as communists allowed many to ignore the human right breaches of the South African regime. Most of the activists belonged to left-wing groups or the labour movement, and the relative absence of religious organisations and the Students’ Council of the University of Iceland is notable. Embedded in the transnational anti-apartheid network with particular ways of organisation and mobilisation, the activists became emotionally engaged and worked for a moral cause.